The effect of remanufacturing and direct reuse on resource productivity of China's automotive production. (1st September 2018) - Liu, Bomin; Chen, Dingjiang; Zhou, Wenji; Nasr, Nabil; Wang, Tao; Hu, Shanying; Zhu, Bing
Abstract: Remanufacturing and direct reuse are considered important measures for promoting the circular economy and improving resource efficiency. Automotive production is a typical resource- and energy-intensive industrial sector, and is a prime market for remanufacturing and direct reuse. Assessing the effect of remanufacturing and direct reuse on the automotive production industry from the perspective of resource efficiency will provide an important reference for improving understandings of remanufacturing and guiding relevant policies in a broader context. A literature review reveals few studies focusing on the resource efficiency of remanufacturing and direct reuse, and the relative lack of a generally accepted indicator to assess the resource efficiency of industrial processes. This paper promotes a new indicator, resource productivity of industrial process, and constructs a material flow model to calculate the resource productivity of China's automotive industry. Results suggest that the indicator and its analytical model are effective tools to assess resource efficiency. Results also suggest that compared to a case where remanufacturing and direct reuse are not employed, adding these processes in China's automotive supply chain would increase resource productivity of industrial process by 7.1% in a high efficiency scenario. Based on these findings, policy recommendations for applying the indicator at industry level and encouraging remanufacturing and direct reuse are provided. Highlights: Resource productivity of industrial process indicator is developed and demonstrated. A material flow model for China's automotive production is constructed. Effect of remanufacturing and direct reuse on resource productivity is evaluated.